2020
DOI: 10.3389/fvets.2020.572906
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability and Bioefficacy of Hemp By-Products in Ruminant Meat Production and Preservation: A Review

Abstract: Plant by-products obtained from agro-industrial processes require valorisation to demonstrate their potential for enhancing animal health, meat production, and shelf life extension. One example is the fast-growing hemp industry, which produces seeds, leaves, seed oil, and cake. Studies on the nutritional value of hempseed cake have shown it can be a valuable source of protein in ruminant diets. However, there is limited documentation on the bioavailability and bioefficacy of hemp phytochemicals for improving r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 121 publications
(234 reference statements)
1
39
2
Order By: Relevance
“…(EC) 767/09, takes into account a maximum content of Δ 9 ‐THC equal to 0.2%. The ash amount registered in the study for all samples was higher compared to the literature data (Callaway, 2004 ; Semwogerere et al, 2020 ) in particular for FR and FT. A lot of factors such as botanical species, type of soil, fertilization, harvesting and processing methods could affect the mineral profile of samples (McDonald et al, 2011 ).…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…(EC) 767/09, takes into account a maximum content of Δ 9 ‐THC equal to 0.2%. The ash amount registered in the study for all samples was higher compared to the literature data (Callaway, 2004 ; Semwogerere et al, 2020 ) in particular for FR and FT. A lot of factors such as botanical species, type of soil, fertilization, harvesting and processing methods could affect the mineral profile of samples (McDonald et al, 2011 ).…”
Section: Discussioncontrasting
confidence: 65%
“…Regarding chemical composition, the data of hemp co‐products of this study agreed to that reported in literature (Alaru et al, 2011 ; Gibb et al, 2005 ; Vonapartis et al, 2015 ) for flower and seeds co‐products. In this regard, hemp co‐products chemical composition, particularly of seeds, could be comparable to soybean meal ones (Semwogerere et al, 2020 ). Indeed, taking into count the high protein content and considering the high amount of essential amino acids reported by House et al ( 2010 ) for similar substrates, all tested co‐products could be evaluated as a source of high‐quality protein.…”
Section: Discussionmentioning
confidence: 99%
“…The surface of hempseed in Europe, estimated by European Industrial Hemp Association (EIHA) [ 5 ], was about 50,081 hectares in 2018 with an increase of 3.3%, 70%, and 614% compared with 2017, 5-years average and 1993, respectively. The major producers in the world are Canada and USA with an estimated 315,000 and 1160 hectares respectively, as reported by Semwogerere et al [ 6 ].…”
Section: Introductionmentioning
confidence: 91%
“…For this purpose, various types of oleaginous seeds are used, in the form of whole seeds, flours, refined and unrefined oils, and oil-pressing by-products including oilseed cake, meal, and protein isolates or hydrolysates derived from, for instance, black cumin seeds, flax, pumpkin, sesame, and sunflower seeds [ 2 , 3 , 4 , 5 ]. In recent years, there has also been growing interest in the use of hemp seeds and hemp oil in feed production and vegan foods, as well as the enrichment of bakery and dairy food products with hemp ingredients, but only few research has been dedicated to meat products [ 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…When the oil is extracted with organic solvents from roasted seeds, this type of by-product is called a post-extraction meal. Hemp cake, as a by-product of cold pressing oil from hemp seeds, is a less processed ingredient, rich in protein, fiber, minerals, and biologically active compounds [ 7 , 11 ], and may be used for the production of new or reformulated meat products that will be perceived by consumers as healthier. Such products can also be perceived by consumers as more “environmentally friendly”, as they contain less animal raw materials and allow the use of valuable by-products for purposes other than the production of feed or waste.…”
Section: Introductionmentioning
confidence: 99%